Enhanced corrosion resistance of plasma electrolytic oxidation coatings prepared on Mg alloy ZX using nano-Al2O3 and NaF incorporated electrolyte. (1st February 2021) - Soliman, H.; Ahmed, M. K.; Elbadewy, R.
ABSTRACT: The corrosion resistance of Mg–alloys 3%Zn–0.8%Ca is enhanced by plasma electrolytic oxidation (PEO) through doping two kinds of nano-additives (NaF and Al2 O3 ) in the silicate electrolyte. Those additives yielded less roughness-compact films composed of higher intensity of stable MgO phase, consequently corrosion resistance enhancement. Nano-ceramic Al2 O3 exhibited more isolation than NaF for ZX alloy due to the high tendency to oxidize Mg to MgO through a direct step. On the other side, NaF needs two steps to form MgO passing by an intermediate phase. The mechanism for the additives influence will be discussed in detail on the light of morphological characteristics, XRD and their corrosion behaviour. GRAPHICAL ABSTRACT: